General theory eh ondulyatornyh induction acceleration systems - Куліш, В.В.; Губанов, І.В.; Марінченко, Г.Є.; Бруснік, А.Ю. (Proceedings of National Aviation University (archive), 2006)
Universal theoretical model within which it is possible quantitative description of ЕН-accelerators and similar devices on their basis is built (ЕН-systems). Description of such universal model is offered to realize within the theory of hierarhial ossilations and waves. For solution of nonlinear tasks of theory of the ЕН-systems is offered to use the hierarchical versions of method of Bogolubov, method of averaged equation for the current density and method of hierarchical transformation of coordinates.